2007
DOI: 10.1111/j.1540-8167.2007.01023.x
|View full text |Cite
|
Sign up to set email alerts
|

The Morphology Changes in Limb Leads after Ablation of Verapamil‐Sensitive Idiopathic Left Ventricular Tachycardia and Their Correlation with Recurrence

Abstract: Successful radiofrequency ablation of ILVT could result in morphology changes in limb leads of ECG, especially in inferior leads. The combined changes in inferior leads can be used as an effective endpoint in ablation of this ILVT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
5
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 18 publications
2
5
0
Order By: Relevance
“…Finally, a few groups have suggested the creation of partial or complete LPF block as a reproducible, easily demonstrable electrophysiological end point for LPFVT ablation. 7 , 14 , 19 In our study, the development of complete LPF block was associated with more basally located ablations. Furthermore, the formation of LPF block did not reduce the risk of LPFVT recurrence.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Finally, a few groups have suggested the creation of partial or complete LPF block as a reproducible, easily demonstrable electrophysiological end point for LPFVT ablation. 7 , 14 , 19 In our study, the development of complete LPF block was associated with more basally located ablations. Furthermore, the formation of LPF block did not reduce the risk of LPFVT recurrence.…”
Section: Discussionsupporting
confidence: 52%
“…Through detailed electrophysiological studies (EPS), FVT has been determined to be reentrant in mechanism, can be responsive to verapamil, involves various branches of Purkinje network emanating from left fascicles with differential conduction properties participating in the tachycardia, and can be successfully treated by localized ablation in the LV septum. 2 14 On the basis of reports of small single-center cohorts undergoing ablation, acute success rates are generally high although limited data exist about electrophysiological findings and clinical outcomes in the few patients who do develop arrhythmia recurrence. More recently, case reports have described patients with FVT representing years after ablation with different variants of FVT.…”
mentioning
confidence: 99%
“…and not due to progesterone alone, the ease of arrhythmia induction in the second study was impressive to suggest a correlation. Post ablation, there were fresh q waves in inferior leads, indicating the efficacy of ablation, as reported by Yao et al 13 …”
Section: Discussionsupporting
confidence: 77%
“…Previous studies considered the achievement of morphology changes or LPFB on surface ECG in SR as an effective endpoint of RFCA for ILVT 4,7,8 . It was reported that the development of LPFB was associated with a high procedural success rate and new‐onset LPFB recovery could be a predictor of ILVT repeat procedure 8 .…”
Section: Discussionmentioning
confidence: 99%
“…Radiofrequency catheter ablation (RFCA) can eliminate ILVT in most cases by targeting the presystolic Purkinje potential (PP) or diastolic potential (DP) during tachycardia, 1,2 or by targeting the retrograde PP during sinus rhythm (SR) 3 . During ablation of ILVT, changing of cardiac axis deviation in SR has been reported to be one of the markers for a successful catheter ablation of ILVT 4,5 . The purpose of this study is to investigate the incidence, mechanism of a change of cardiac axis deviation in SR or during ILVT after or during RFCA and to further clarify an appropriate approach for catheter ablation of ILVT.…”
Section: Introductionmentioning
confidence: 99%